Internal Business Success Factors of Small and Medium-Sized Enterprises in Russia - NIKOLAEVA, Ekaterina; PLETNEV, Dmitry (Journal of Advanced Research in Law and Economics, 2017)
The paper analyzes the internal success factors of small and medium-sized business in Russia. Special attention is paid to the research of financial factors as the most significant in business performance. The authors find the effect of various financial indicators of corporate performance on business success using accounting statements. The analysis of small and medium-sized business is conducted by federal districts of the Russian Federation. Key significant internal financial factors are revealed as ensuring the success of small and medium-sized business. On the basis of the factors so revealed, recommendations are made for improvement of small and medium-sized business.